2013
DOI: 10.1021/la400037c
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Carbon Black Stabilized Oil-in-Water Emulsions to the Addition of Surfactant Solutions

Abstract: We use carboxyl-terminated, negatively charged, carbon black (CB) particles suspended in water to create CB-stabilized octane-in-water emulsions, and examine the consequences of adding aqueous anionic (SOS, SDS), cationic (OTAB, DTAB), and nonionic (Triton X-100) surfactant solutions to these emulsions. Depending upon the amphiphile's interaction with particles, interfacial activity, and bulk concentration, some CB particles get displaced from the octane-water interfaces and are replaced by surfactants. The em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 42 publications
0
56
0
Order By: Relevance
“…Another strategy for displacing particles from drop surfaces is to add surfactant which competes for the oil-water interface [32,33,34]. Vella et al [35] observed that adding surfactant could disrupt particle layers attached to planar water surfaces.…”
Section: Detaching Particles From Fluid Interfacesmentioning
confidence: 99%
See 3 more Smart Citations
“…Another strategy for displacing particles from drop surfaces is to add surfactant which competes for the oil-water interface [32,33,34]. Vella et al [35] observed that adding surfactant could disrupt particle layers attached to planar water surfaces.…”
Section: Detaching Particles From Fluid Interfacesmentioning
confidence: 99%
“…Katepalli et al [33] argued that surfactant addition will cause particle displacement from a drop (of radius, r d ) if a surfactant-stabilised drop (of the same radius) has a lower free energy than the particle-stabilised drop. Thus adding surfactant causes particle displacement due to the emulsion system seeking a lower energy state.…”
Section: Detaching Particles From Fluid Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…10 In cases where the particles are attracted to the interfaces, emulsions may be either stabilized or destabilized by the interactions between the particles and surfactants. [11][12][13][14][15] For example, Whitby et al reported on the ability of anionic surfactant to destabilize Pickering emulsions prepared with hexadecylsilane modified silica when added at concentrations greater than the critical micelle concentration (CMC). 13 In cases where synergistic stabilization of the emulsions exist, the effect may be attributed to surfactant-induced flocculation of the particles leading to greater steric hindrance to coalescence, or enhanced 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 stabilization due to lowering of the interfacial tension between the oil and water phases without a significant loss of particles from the interface.…”
Section: Introductionmentioning
confidence: 99%